Pinostrobin, a fingerroot compound, regulates miR-181b-5p and induces acute leukemic cell apoptosis - Norkaew C. (2023)
Pinostrobin (PN) is the most abundant flavonoid found in fingerroot. Although the anti-leukemic properties of PN have been reported, its mechanisms are still unclear. MicroRNAs (miRNAs) are small RNA molecules that function in posttranscriptional silencing and are increasingly being used in cancer therapy. The aims of this study were to investigate the effects of PN on proliferation inhibition and induction of apoptosis, as well as the involvement of miRNAs in PN-mediated apoptosis in acute leukemia. The results showed that PN reduced cell viability and induced apoptosis in acute leukemia cells via both intrinsic and extrinsic pathways. A bioinformatics approach and Protein-Protein Interaction (PPI) network analysis revealed that ataxia-telangiectasia mutated kinase (ATM), one of the p53 activators that responds to DNA damage-induced apoptosis, is a crucial target of PN. Four prediction tools were used to predict ATM-regulated miRNAs; miR-181b-5p was the most likely candidate. The reduction in miR-181b-5 after PN treatment was found to trigger ATM, resulting in cellular apoptosis. Therefore, PN could be developed as a drug for acute leukemia; in addition, miR-181b-5p and ATM may be promising therapeutic targets.